2013
DOI: 10.1002/2013jc009464
|View full text |Cite
|
Sign up to set email alerts
|

An exchange flow between the Okhotsk Sea and the North Pacific driven by the East Kamchatka Current

Abstract: A new mechanism for driving the water mass exchange between the Okhotsk Sea and the North Pacific is presented. This exchange flow originates from the East Kamchatka Current (EKC), a western boundary current of the subpolar gyre, and occurs through the two deepest straits of the Kuril island chain, the Kruzenshtern and Bussol straits. An inflow toward the Okhotsk Sea occurs at the northern Kruzenshtern strait and an outflow toward the North Pacific occurs at the southern Bussol strait. By using the Kelvin's Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…During the spring 2018 dust events, positive CHL-a anomaly areas were distributed around the Kuril Islands (Figure 7c), which are known as the area with strong physical mixing occurring [108][109][110], leading to supply of nutrients to the surface waters for phytoplankton growth. To examine the influence of physical mixing on CHL-a variation in the area, we analyzed non-dust spring 2017 CHL-a and MLD data in the same area represented in the present study (see blue square in Figure 7c, showing AI > 1.7 that indicates the occurrence of a dust event) ( Figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…During the spring 2018 dust events, positive CHL-a anomaly areas were distributed around the Kuril Islands (Figure 7c), which are known as the area with strong physical mixing occurring [108][109][110], leading to supply of nutrients to the surface waters for phytoplankton growth. To examine the influence of physical mixing on CHL-a variation in the area, we analyzed non-dust spring 2017 CHL-a and MLD data in the same area represented in the present study (see blue square in Figure 7c, showing AI > 1.7 that indicates the occurrence of a dust event) ( Figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…The Sea of Okhotsk is characterized by low temperature and segregated by the Kuril Island chain from the North Pacific Ocean. The Kruzenshtern and Bussol Straits, two major passages in the Kuril Island chain, enable the exchange of flow between the Sea of Okhotsk and the North Pacific Ocean ( Kida and Qiu, 2013 ). Furthermore, the strong mixing of water of the East Kamchatka Current (one branch of the Bering slope current), with water from the Okhotsk Sea at the Bussol Strait, plays a major role in the transformation of the East Kamchatka Current to the Oyashio Current ( Ohtani, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using Eq. (4), Kida and Qiu (2013) assumed a frictional balance between the stresses exerted by a Throughflow and that by the WBC and showed that the magnitude of the Throughflow transport U scales as…”
Section: A Frictional Balance Around An Islandmentioning
confidence: 99%
“…By applying Eq. (4) for two islands and by assuming the same frictional balance between the flow through the straits and the WBC as in Kida and Qiu (2013), we derive two equations, …”
Section: A Frictional Balance Around An Islandmentioning
confidence: 99%
See 1 more Smart Citation